2012
DOI: 10.3390/bs2020135
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Studies and Genetic Alterations in Corticotropin-Releasing Hormone (CRH) Neurocircuitry: Insights into Human Psychiatric Disorders

Abstract: To maintain well-being, all organisms require the ability to re-establish homeostasis in the presence of adverse physiological or psychological experiences. The regulation of the hypothalamic-pituitary adrenal (HPA) axis during stress is important in preventing maladaptive responses that may increase susceptibility to affective disorders. Corticotropin-releasing hormone (CRH) is a central stress hormone in the HPA axis pathway and has been implicated in stress-induced psychiatric disorders, reproductive and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 151 publications
1
33
0
Order By: Relevance
“…These mouse lines have proven extremely valuable given their ability to reflect different degrees of the activating, arousing and anxiogenic-like properties of CRF (Dedic et al, 2012; Dirks et al, 2002; Kolber et al, 2010; Lu et al, 2008; Refojo et al, 2011; Stenzel-Poore et al, 1994; Vicentini et al, 2009). However, a direct comparison of different CRF overexpressing mouse models reveals substantial discrepancies and inconsistencies, which are largely related to differences in the design of these animal models, including the expression level and the spatio-temporal properties of the utilized promoters driving CRF overexpression (reviewed in: Laryea et al, 2012). Another confounding factor appearing in several CRF overexpressing mouse lines is the hypercorticosteronism accompanied by a Cushing-like phenotype.…”
Section: Dissecting Crh-controlled Neurocircuitries Of Stress and mentioning
confidence: 99%
“…These mouse lines have proven extremely valuable given their ability to reflect different degrees of the activating, arousing and anxiogenic-like properties of CRF (Dedic et al, 2012; Dirks et al, 2002; Kolber et al, 2010; Lu et al, 2008; Refojo et al, 2011; Stenzel-Poore et al, 1994; Vicentini et al, 2009). However, a direct comparison of different CRF overexpressing mouse models reveals substantial discrepancies and inconsistencies, which are largely related to differences in the design of these animal models, including the expression level and the spatio-temporal properties of the utilized promoters driving CRF overexpression (reviewed in: Laryea et al, 2012). Another confounding factor appearing in several CRF overexpressing mouse lines is the hypercorticosteronism accompanied by a Cushing-like phenotype.…”
Section: Dissecting Crh-controlled Neurocircuitries Of Stress and mentioning
confidence: 99%
“…Layer 2/3 neurons respond more robustly in male mice, whereas postsynaptic responses in layer 5 are enhanced in females. TRAP translational profiling (Heiman et al, 2008) revealed that expression of the corticotropin releasing hormone binding protein ( Crhbp ) gene (Van Den Eede et al, 2005), an inhibitor of the stress hormone CRH (Laryea et al, 2012), is specifically enriched in OxtrINs. Upon CRH application, induced activity of male but not female layer 2/3 pyramidal cells in mPFC slice recordings was potentiated.…”
Section: Introductionmentioning
confidence: 99%
“…Outside the hypothalamus and anterior pituitary, CRF 1 are expressed widely in the cortex and cerebellum, hippocampus, amygdala, and bed nucleus of the stria terminalis (BNST) (13). Activation of CRF receptor binding in the amygdala induces fear responses (14), and administration of CRF in animal models produces PTSD-relevant anxiety behaviors, including heightened acoustic startle response, sleep disturbance, and increased conditioned fear response (15). Early life stress in animal models produces hyperactivity of CRF neurons and chronic activation of limbic brain regions (16,17).…”
Section: Introductionmentioning
confidence: 99%